Praktik Pengembangan Program Perhutanan Sosial Sebagai Strategi Pelestarian Kawasan Hutan di Desa Yehembang Kangin - Farkha Alfa Centauri; Tahsa Ayu Seva; Galang Alhaya Dinasti; Hendra Bagus Pamungkas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Along with the pace of development and economic growth in a region, it cannot be separated from various kinds of activities that are at risk of environmental destruction, one of which is forests. Where, this has concretely occurred in the increasing cases of encroachment on forest areas in Jembrana Regency. This encroachment was triggered by